Liver Transplantation Using a Graft from a Donor with Situs Inversus Totalis: A Case Report and Review of the Literature. (10th September 2013) - Sun, Xu-Yong; Qin, Ke; Dong, Jian-Hui; Li, Hai-Bin; Lan, Liu-Gen; Huang, Ying; Cao, Song; Li, Zhuang-Jiang
Abstract : It is critical to effectively use every available organ to meet the increasing demands for liver transplantation. Situs inversus is a rare congenital anomaly caused by obstruction of viscus rotation during embryonic development. Situs inversus was once regarded as a contraindication to liver transplantation because of the technical difficulties associated with the unique vascular anatomy and concern about achieving accurate graft positioning. Here, we present a successful case of liver transplantation using a graft from a donor with situs inversus totalis. The related experience will contribute to opening up new realms for the use of such rare organ resources.